University Partnerships in the Global Business Arena – What Makes Them Successful? Featuring a Current Partnership Example Between U.S. and Moroccan Universities - Wood, Van R.; Benos, William J.; Darban, Karim; Mazón, David Garay (Archives of Business Research, 2024)
University partnerships that join together institutions of higher education located in different parts of the world offer significant opportunities to educate all those involved (students, faculty, governmental agencies and participating private organizations). Students become more aware of the globalized environment in which they live and work; faculty build relations that expand their research opportunities and teaching skills, governmental agencies experience a different perspective on global business possibilities; and private organizations gain insights into world markets from the final reports and recommendations that come from such partnerships. This paper draws upon existing literature focusing on how to create and sustain productive university partnerships located in different countries and describes why such collaborations are central to the future of higher education and global business in general. The authors feature the steps taken to create an ongoing partnership between three universities (two in the United States and one in Morocco), whose students engaged with a private organization (the project’s “client”) seeking global business insights and opportunities. An overview of the project undertaken is also provided. The paper concludes with a call for development of more university based international partnerships and further research into what makes them successful.